Aktivitas Antibakteri Ekstrak Daun Jeruk Purut (Citrus Hystrix DC) Terhadap Bakteri Uji Pada Bakso Bakar: Penelitian - Ginting, Silvia Margaretta br; Purba, Melpa Yusmawati; Tamba, Gelora Betania; Pasaribu, Maria Benedikta; Saragih, Elsa Angelina; Gultom, Endang Sulistyarini; Situmorang, Nurbaity (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Indonesia, as a tropical country, is rich in essential oil-producing plants, including kaffir lime (Citrus hystrix DC). The leaves of Citrus hystrix are known to contain bioactive compounds such as flavonoids, tannins, and alkaloids, which have potential as natural antibacterial agents. This study aimed to evaluate the antibacterial activity of Citrus hystrix leaf extract against bacteria present in grilled meatballs. An in vitro experimental method using the disc diffusion assay was employed. Fresh Citrus hystrix leaves were obtained through purposive sampling from Medan Krio Village, North Sumatra, extracted using 96% ethanol, and tested against bacteria on Mueller Hinton Agar. Chloramphenicol was used as a positive control, while dimethyl sulfoxide (DMSO) served as a negative control. The results showed inhibition zones of 8.02 mm and 7.09 mm for the leaf extract in two separate trials, whereas the positive control exhibited a 29.91 mm inhibition zone, and no inhibition was observed in the negative control. These findings indicate that Citrus hystrix leaf extract possesses significant antibacterial activity against bacteria in grilled meatballs, although it is less potent than synthetic antibiotics. The extract has potential as a natural antibacterial agent for food preservation.